THE INTERNATIONAL CONFERENCE ON SYRIA (“GENEVA-2”): DIFFICULTIES OF INTER-SYRIAN TALKS AND ROLE OF FOREIGN PLAYERS - M. S. Khodynskaya-Golenischeva (Vestnik MGIMO-Universiteta)
The article deals with the difficulties that may arise in organizing "Geneva-2" as well as those that may appear in the course of the Conference itself. It focuses on the inter-Syrian talks that will be aimed at achieving a compromise on the key issues of Syria’s future.The author provides us with a comparative analysis of the Syrian parties' “degree of readiness” to engage in dialogue as well as with a review of the negotiation documents prepared by various factions of the Syrian opposition in which they outline their vision of transition in Syria.Emphasis is made on how outside players with influence on the Syrian sides (USA, France, Turkey, Qatar, Saudi Arabia and others) should act in the case of impasse of talks or difficulties in the implementation of decisions taken. The paper examines the role that Russia must play in order for the Conference to succeed, as well as that of Lakhdar Brahimi, Special Representative of the UN on Syria.The material presented is particularly relevant in the framework of the revival of the political process around Syria, especially in terms of the intensifying efforts to organize the International Conference with the purpose of finding a comprehensive political settlement to the crisis in Syria through the full implementation of the Geneva Communiqué (30 June, 2012).